Spatial and temporal characteristics of gait as outcome measures in multiple sclerosis (EDSS 0 to 6.5) - Lizrova Preiningerova, Jana; Novotná, Klára; Rusz, Jan; Sucha, Lucie; Ruzicka, Evzen; Havrdova, Eva (Journal of neuroengineering and rehabilitation, 2015)
BACKGROUND: Gait impairment represents one of the most common and disabling symptom of multiple sclerosis. Quantification of the gait is an important aspect of clinical trials. In order to identify which temporal or spatial parameters of gait could be used as outcome measures in interventional studies of patients with different levels of disability, we evaluated characteristics of these parameters in MS patients across the whole spectrum of mobility from EDSS 0 to 6.5. METHODS: This is a cross-sectional study of spatial and temporal parameters of gait at self selected speed and at fast speed of walking in 284 patients with multiple sclerosis (108 men, mean age 38 years ± SD 10.8 years, range 18-64) divided into seven levels of disability (EDSS 0 to 1.5, EDSS 2.0 to 2.5, EDSS 3.0 to 3.5, EDSS 4.0 to 4.5, EDSS 5.0 to 5.5, EDSS 6.0, EDSS 6.5). RESULTS: The velocity of gait decreases with increasing EDSS levels. Hovewer, the spatio-temporal parameters of gait that are involved in this process differ across the EDSS levels. The step length is decreased at higher EDSS levels up to the EDSS 6.0, but was not different between EDSS 6.0 and 6.5. The step time is significantly longer at EDSS 6.0 and 6.5, while the step length remains the same at those levels. The increase in percentage of double support time becomes statistically significant at EDSS 3.0-3.5 and continues to increase until EDSS 6.5. Variability of step time, step length or step width did not show significant difference between studied EDSS levels. CONCLUSIONS: There is no single spatio-temporal parameter of gait (other than velocity of gait) that would show significant differences among all levels of EDSS. The step length reflects shortening of steps at lower EDSS levels (2.0 to 6.0), and percentage of double support time better reflects changes at higher EDSS levels 3.0 - 6.5. Gait variability is not associated with disability in MS and therefore would not be a suitable outcome measure. These observations have to be considered when designing gait experiments with temporal and spatial parameters of gait as outcomes.
Keywords: Gait Disorders, Neurologic; lidé; mladiství; Adult; Middle Aged; Walking; Persons with Disabilities; stupeň závažnosti nemoci; Multiple Sclerosis; Female; chůze; Adolescent; Humans; průřezové studie; Cross-Sectional Studies; roztroušená skleróza; hodnocení výsledků zdravotní péče; neurologické poruchy chůze; lidé středního věku; mužské pohlaví; Gait; ženské pohlaví; Severity of Illness Index; Male; Outcome Assessment, Health Care; postižení; dospělí; chůze (způsob)